Myrcene—What Are the Potential Health Benefits of This Flavouring and Aroma Agent? - Surendran, Shelini; Qassadi, Fatimah; Surendran, Geyan; Lilley, Dash; Heinrich, Michael (Frontiers in Nutrition, 2021)
Myrcene (β-myrcene) is an abundant monoterpene which occurs as a major constituent in many plant species, including hops and cannabis. It is a popular flavouring and aroma agent (food additive) used in the manufacture of food and beverages. This review aims to report on the occurrence, biological and toxicological profile of β-myrcene. The main reported biological properties of β-myrcene - anxiolytic, antioxidant, anti-aging, anti-inflammatory, analgesic and anti-diabetic properties – are discussed, with the mechanisms of activity. Here we also discuss recent data regarding the safety of β-myrcene. Overall, β-myrcene has shown promising health benefits in many animal studies. However, studies conducted in humans is lacking. In the future, there is potential for the formulation and production of non-alcoholic beers, functional foods and drinks, and cannabis extracts (low in THC) rich in β-myrcene.